Analisis Komparasi Kinerja Obligasi Syariah dengan Obligasi Konvensional di Bursa Efek Indonesia (BEI) Tahun 2010-2013 - B41111150, Safitri Akbari (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
This research aims to know whether there is significant difference between sharia obligation performance and conventional obligation performance. The difference between two obligations is measured by Current Yield, Yield to Maturity (YTM) score, and measuring the obligation risk level based on the rating. The sample of this research is the obligation that is published by non-finance company, which is registered in Bursa Efek Indonesia (BEI) in 2010-2013 period. The data is collected by using Purposive Sampling Method. There are 21 obligations which are selected as the sample of this research. Analyzing the data is done by using SPSS 20 aplication, with analyzing testing by using Independent Sample T-Test. The testing result show that there is significant different between sharia obligation performance and conventional obligation performance based on Current Yield, Yield to Maturity (YTM). However, in the obligation risk level based on the rating, there is no significant different between sharia obligation risk and conventional obligation risk.